Photon counting principle in cathodic-electrochemiluminescence - Dahal, Suman (My University, 2020)
The cathodic-electrochemiluminescence is the procedure where the electrical excitation is provided through the cathode electrode to a chemical solution, which produces luminescence. As the cathodic-electrochemiluminescence is a relatively new research topic, no commercial instrumentation is available for analyzing the output signal. Researches have been carried out for the past decade to implement cathodic-electrochemiluminescence in human and veterinary medical diagnostical purposes. In the cathodic-electrochemiluminescence principle, whole blood samples or serum are diluted in a solution and measured through the procedure. As a result, a small amount of light is generated, collected, and read as a single photon. Thus, a proper single photon-counting circuit and the excitation circuit must detect produced light and convert it into a human-readable format. This thesis is based on the design, development, and implementation of embedded software for the single-photon counting procedure and an excitation circuit during the cathodic-electrochemiluminescence. The single-photon counting principle implementation is only possible through the photomultipliers tube. Photomultiplier tubes are photon detectors that convert low energy photons to electrical signals, which can be collected and read as single photons. These single photons are then summed in a time-resolved solution to count as emission photons used to measure different analytes concentration. In contrast, implementing a photomultiplier tube in single-photon counting procedures brings the challenges of incorporating the functionality without decreasing the output signal's sensitivity. Besides, the limit of detection for some of the bioanalytical application is too low, which is affected by the noise created by the photomultiplier tube's operation. Nevertheless, the implementation is PMT dependent, and the output signal has been optimized for the cathodic electrochemiluminescence principle. The implementation result shows that the system is capable of counting single-photons in low-level bioanalytical applications. The system can be implemented in instrumentation required in the medical, veterinary, and environmental sectors.
Keywords: photomultiplier tubes, cathodic-electrochemiluminescence, single-photon, photon-counting principle